Explanation of the express method of the determination of steel grade by spark - Nikiforov, Igor; Maltsev, Pavel; Ivanov, Vladimir; Barsuk, Inna (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
On the basis of physico-chemical theory of burning metal particles, the explanation known method of determining the grade of steel for the spark when it is grinding is performed. The features of formation of globules are reviewed and given them a brief description. The conditions for the formation of a spark in the processing of steels and alloys of various grades are researched.